Outcome of instrumental vaginal delivery in university of Abuja teaching hospital: a five-year review - Henderson Jumbo, Caroline T.; Ayogu, Malachy E.; Abdullahi, Habiba I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Most women will achieve spontaneous vaginal delivery; however, a few will need assistance in form of Instrumental vaginal delivery (IVD). These are employed to shorten the second stage on labour and to minimize the incidence of cesarean section. The aim of the study was to determine the prevalence and outcomes of instrumental vaginal delivery at the University of Abuja teaching hospital. Methods: This was a retrospective study of women who had instrumental vaginal delivery over a 5-year period at the University of Abuja teaching hospital. Data on socio-demographic variables, type of instrumental delivery performed, Apgar scores of neonates delivered, indications and complication were obtained from the labour ward registers and case notes of patients and entered into a proforma and analysed using SPSS software for Windows version 23. Results: Instrumental vaginal delivery (IVD) rate performed for both Vacuum or Forceps) was 0.99%, Forceps delivery was 0.30% and vacuum accounted for 0.69% of all deliveries. The mean maternal age was 27.53±5.5 years and 51 (54.8%) of the parturient were primigravidae, 55 (59.1%) were booked patients. Delayed second stage of labour (38.7%) was the most common indications for IVD. Maternal complications noted were genital tract laceration 17 (18.3%) and primary post-partum haemorrhage 10 (10.8%). The mean APGAR scores was 6 and 8 in the first and fifth minutes respectively, live births were 85 (91.4%), stillbirths were 7 (7.5%) and one early neonatal death was recorded (1.1%) due to asphyxia as a result of difficult forceps delivery. Conclusions: The IVD rate at UATH is low with good maternal and fetal outcome and preference for vacuum delivery.